A survey on exploring the challenges and applications of wireless body area networks (WBANs) - Arun Sekar Rajasekaran; L. Sowmiya; Azees Maria; R. Kannadasan (Cyber Security and Applications)
Networks play an important role in the day-to-day life of every individual. Networks are involved in the transmission of necessary information between the sender and receiver in the channel. Wireless Body Area Network (WBAN) is a major advancement in the field of network communication. Due to the arrival of the Micro Electromechanical System (MEMS) and several intelligent sensors, collaboration with WBAN makes accurate predictions of parameters in the human body. WBAN has numerous applications in medical and non-medical fields. WBANs have demonstrated remarkable capabilities in real-time health monitoring, facilitating the collection of vital physiological data from individuals in diverse environments. Firstly, their low-power and energy-efficient design ensures prolonged device operation, making them suitable for continuous monitoring over extended periods. Additionally, the miniaturization of sensors and the integration of wireless communication technologies enable seamless data transmission to centralized healthcare systems. Furthermore, the integration of artificial intelligence and machine learning algorithms in WBAN systems has enabled personalized health analytics, allowing for more precise and context-aware health monitoring. This paper gives a survey of the WBAN standard, security in WBAN, several authentication approaches, routing, and MAC protocols. In addition, this paper describes the challenges faced by WBAN, such as network partitioning, changes in postures, lifetime issues, and quality of service (QoS). At last, the advancement in WBAN is for future improvement in the area of body area networks.